IUCN Red List: over 6000 dragonfly species assessed - Clausnitzer, Viola (2022)
Following the most recent update of the IUCN Redlist (IUCN, 2021), as of 9th December 2021, the number of species at risk of extinction on the Red List has exceeded 40,000 for the first time. The IUCN Red List now includes 142,577 species of which 40,084 are threatened with extinction. However, of the largest of all organism groups, the insects, only 12,100 species have been assessed so far. The complete dragonfly assessment contributes almost 50% to this number (6,016 species). The assessment was completed by members of the IUCN SSC Dragonfly Specialist Group co-chaired by Viola Clausnitzer and Federico Lozano.